The Role of Government in Off-Grid Rural Electrification Based on Renewable Energy in Indonesia - Nashiruddin Haramaini, Muhammad; Anggoro, Yudo (The Indonesian Journal of Business Administration, 2017)
Abstract. Until the end of 2015, Indonesia's electrification ratio only reached 88.3% leaving the part of nation communities not enjoyed electricity. Most of them located in remote village, border-states area and isolated islands. The electricity system in Indonesia which only involves little private sector cause the rural electrification rely on the shoulders of the government. The government choose to implement rural electrification programs based on renewable energy (RE). This role is carried out by the Directorate General of New and Renewable Energy and Energy Conservation. The purpose of this program is mainly to increase the electrification ratio while promoting RE as a solution for remote villages. This study aims to understand the policy implementation according to the policy cycle. The advantages of qualitative methods used to collect and analyze data. Indonesia multilevel system of government and involving multi-stakeholders has been a challenge for the implementation of this policy. Unfortunately the government was only set short-term goals, to increase the electrification ratio. Rural communities as a user and a major stakeholder not fully engaged and have only treated as an object of beneficiaries. The low engagement of rural communities become major barrier for the sustainability of RE rural electrification program. The recommendation from the findings are to redesign the program to be consistent with sustainability indicator developed with logic model approach.Keywords: renewable energy, rural electrification, public policy, sustainability.